Penerapan Model Discovery Learning untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Kelas IV SD Negeri Kalinongko - Aida Maulidina; Muflikhul Khaq; Cahyo Apri Setiaji (Jurnal Kualita Pendidikan, 2021)
This study aims to determine whether there is an increase in student motivation and learning outcomes by applying the Discovery Learning model in social studies for grade IV SD Negeri Kalinongko for the 2020/2021 academic year. This research was conducted in November 2020. This research is a Classroom Action Research (PTK). The subjects in this study were all 11 students of grade IV. Collecting data in this study using observation sheets, interviews, test results and evaluation, questionnaires and documentation. The data analysis used was descriptive qualitative and quantitative analysis. The research was conducted for 2 cycles and ended in cycle 2 with the results of the analysis showing that the application of the Discovery Learning model can increase student motivation and learning outcomes. The results of the analysis of student learning motivation reached 77% in the "Good" category and the results of the analysis of student tests and evaluations reached 93% so that these results have reached indicators of success.